THE ROLE OF SUSTAINABILITY IN ASEAN BANKING DESICION-MAKING: A SYSTEMATIC LITERATURE REVIEW - Izzalqurny, Tomy Rizky; Utami, Helianti; Cahyani, Yasintha Dwi; Rahma, Shelyra Leovita Dwi; Althof, Zahwa Aqila (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2025)
This study examines the growing importance of sustainability as a foundation for strategic decision-making in the ASEAN banking sector, which is characterized by regulatory, cultural, and institutional diversity. It aims to explore how Environmental, Social, and Governance (ESG) principles are understood and integrated into banking decision-making and to assess their contributions to efficiency, stability, and institutional legitimacy. Using a Systematic Literature Review (SLR) based on the PRISMA 2020 protocol, this study analyzes 22 Scopus-indexed articles published between 2019 and 2025. The findings indicate that ESG serves as a strategic framework that enhances credit quality, operational efficiency, and risk management, with governance emerging as the most influential dimension in successful sustainability integration. The effectiveness of ESG implementation is moderated by institutional and cultural contexts across ASEAN countries. This study contributes by identifying gaps in the literature and proposing a contextual ESG framework for the ASEAN banking sector, providing insights for regulators and practitioners in developing adaptive and inclusive sustainable finance policies.